ZOOBENTHOS COMMUNITY STRUCTURE IN THE MANGROVE AREA OF THE SUNGAI RAWA VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY - Agustini, Agustini; Adriman, Adriman; Fajri, Nur El (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractZoobenthos commonly attached in the roots, stems, leaves and substrate in the mangrove area of the Sungai Rawa village. A study aims to understand the structure of zoobenthos community in that area has been conducted in April-Mei 2019. Zoobenthos were collected manually in 3 station, namely station 1 (mangrove ecotourism), station 2 (harbor and settlement), and station 3 (natural ecosystem). Water quality parameters measured were temperature, salinity, pH, dissolved oxygen, and sediment fraction and organic matterials content in sediment. There were 13 types of zoobenthos found in the study area, they were belonged to 4 classes, namely Gastropoda (8 species), Polychaeta (2 species), Bivalvia (2 species) dan Malacostraca (1 species). Zoobenthos density ranges from 1,4074-4,5556 organisms/m2. The species diversity index(H’) ranged from 1,66–3,06, uniformity index (E) ranged from 0,57–0,85 dan dominance index (C) ranged from 0,16–0,44. Water quality parameters values in mangrove area were as follows: temperature 28–31 °C, salinity 24–29 ‰, water pH 6-7, soil pH 6,2-6,6, dissolved oxygen 5,2–6,8 mg/L. The sediment was sandy mud to mud with organic materials 33,98–49,47 %. Keywords: Mangrove ecosystem, Zoobenthos community, Epifauna, Sediment